Characterizing the Genetic Diversity of Salmonella Isolated from U.S. Raw Inshell Pistachios Using Whole Genome Sequencing - Erika M. Estrada; Anne-laure Moyne; Linda J. Harris (Journal of Food Protection, 2023)
The genetic diversity of 169 Salmonella isolates from pistachios collected from California storage silos during the 2010, 2011, and 2012 harvests (silo survey isolates) was determined by analyzing the whole genome sequence data using the CFSAN SNP pipeline developed by the U.S. Food and Drug Administration’s Center for Food Safety and Applied Nutrition. Salmonella isolates clustered by serovars Agona, Enteritidis, Montevideo, Sandiego, Senftenberg, Liverpool, Tennessee, and Worthington in the phylogenetic tree. Within each serovar, isolates grouped into one or two clusters (≤14 SNPs). Two distinct clusters (>14 SNPs; A and B) were identified for Salmonella Enteritidis, Montevideo, and Liverpool for a total of 11 unique strains. Sequences of representative silo survey isolates clustered with sequences of Salmonella strains isolated from U.S. pistachio-associated samples collected between 2008 and 2018 available on the National Center for Biotechnology Information database, and, in all but two cases, not with sequences of Salmonella strains recovered from raw California almonds from 2001 through 2013. The genomic evidence suggests that strains of Salmonella Agona, Liverpool Cluster A, Montevideo Clusters A and B, Senftenberg, and Worthington have persisted in the California pistachio environment for ≥3 years and some of these strains have been reported exclusively in association with pistachios.